Polyphosphinoborane Block Copolymer Synthesis Using Catalytic Reversible Chain‐Transfer Dehydropolymerization. Issue 3 (8th December 2022) - Race, James J.; Heyam, Alex; Wiebe, Matthew A.; Diego‐Garcia Hernandez, J.; Ellis, Charlotte E.; Lei, Shixing; Manners, Ian; Weller, Andrew S.
Abstract: An amphiphilic block copolymer of polyphosphinoborane has been prepared by a mechanism‐led strategy of the sequential catalytic dehydropolymerization of precursor monomers, H3 B ⋅ PRH2 (R=Ph, n‐hexyl), using the simple pre‐catalyst [Rh(Ph2 PCH2 CH2 PPh2 )2 ]Cl. Speciation, mechanism and polymer chain growth studies support a step‐growth process where reversible chain transfer occurs, i.e. H3 B ⋅ PRH2 /oligomer/polymer can all coordinate with, and be activated by, the catalyst. Block copolymer [H2 BPPhH]110 ‐ b ‐[H2 BP(n‐hexyl)H]11 can be synthesized and self‐assembles in solution to form either rod‐like micelles or vesicles depending on solvent polarity. Abstract : Amphiphilic block copolymers of polyphosphinoboranes, [H2 BPPhH]110 ‐ b ‐[H2 BP(n‐hexyl)H]11, have been prepared by a mechanism‐led strategy of the catalytic reversible chain transfer dehydropolymerization of precursor monomers, H3 B ⋅ PRH2 (R=Ph, h‐hexyl). These self‐assemble in THF:hexane solutions to form nanostructured rod‐like micelles, the morphology of which can be controlled by solvent polarity.